Frequency and morphological behaviour of nouns in Czech and Russian - Mačutek, Ján; Koščová, Michaela; Kelih, Emmerich; Čech, Radek (Bohemistyka, 2023)
Declensional morphology of nouns in Czech and Russian is investigated and compared. It is shown that, in general, word forms which are more similar to their lemmas are preferred, but there are differences between animate and inanimate nouns and also among grammatical genders. The frequency distribution of grammatical cases is also studied, with animacy and gender being again important factors.